Noise performance improvements and tribological consequences of a pad-on-disc system through groove-textured disc surface. (October 2016) - Wang, D.W.; Mo, J.L.; Liu, M.Q.; Ouyang, H.; Zhou, Z.R.
Abstract: In this work, disc surfaces with two kinds of groove configurations are tested in a pad-on-disc system. The experimental results show that cutting 45° grooves on the disc surface can significantly reduce the friction noise. The main reasons are believed to be that the groove-textured surface can trap wear debris and redistribute the contact pressure and thus modify the friction shear stress. Moreover, numerical analysis is performed to simulate the experimental process and a possible mechanism is provided to explain the effect of grooved disc surface on the tribological properties and squeal generation. The groove-textured surface can significantly affect the contact pressure distribution of the pad surface and the transportation of wear debris at interface, and consequently reduce the squeal. Graphical abstract: Highlights: The effect of grooved disc surfaces on friction and wear, and noise is studied. Dynamic transient analysis simulates vibration between pad and grooved disc surfaces. The contact pressure distributions and the relative pad-groove position are studied. The ability of groove in entrapping wear debris and its affect on noise is studied. A noise reduction mechanism for grooved disc surface is proposed.